Reflections on english language teaching and bilingualism in colombia (2012)
According to an article published by one of the leading British newspapers The Daily Telegraph, (27 October, 2010)“Leaders of India's low-caste Dalits are to celebrate the opening of a temple shaped like a desktop computer to inspire "untouchable" children to improve their prospects in life by learning English,”believing that learning English will open up new opportunities for India's 160 million Dalits in higher education and high-status government careers. This is mirrored by the assumption in Colombia and in other Latin American countries that English is the key to success, or citing the title of the successful English language programme adopted by the Ministry of Education in Chile, “InglésAbrePuertas”.In this article I would like to first critique this often unquestioned belief about the development of English and better life prospects. I will then talk briefly about the relationship between English Language Teaching (ELT) and the development of bilingualism. Finally I will discuss how far initiatives such as the English Immersion Programme in San Andrés help to develop bilingual teachers´ competencies.